Multiplexed detection of respiratory pathogens with a portable analyzer in a “raw-sample-in and answer-out” manner - Nan Li (Nature Publishing Group, 2021)
Abstract Coronavirus disease 2019 (COVID-19) has emerged, rapidly spread and caused significant morbidity and mortality worldwide. There is an urgent public health need for rapid, sensitive, specific, and on-site diagnostic tests for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. In this study, a fully integrated and portable analyzer was developed to detect SARS-CoV-2 from swab samples based on solid-phase nucleic acid extraction and reverse transcription loop-mediated isothermal amplification (RT-LAMP). The swab can be directly inserted into a cassette for multiplexed detection of respiratory pathogens without pre-preparation. The overall detection process, including swab rinsing, magnetic bead-based nucleic acid extraction, and 8-plex real-time RT-LAMP, can be automatically performed in the cassette within 80 min. The functionality of the cassette was validated by detecting the presence of a SARS-CoV-2 pseudovirus and three other respiratory pathogens, i.e., Klebsiella pneumoniae, Pseudomonas aeruginosa, and Stenotrophomonas maltophilia. The limit of detection (LoD) for the SARS-CoV-2 pseudovirus was 2.5 copies/μL with both primer sets (N gene and ORF1ab gene), and the three bacterial species were successfully detected with an LoD of 2.5 colony-forming units (CFU)/μL in 800 μL of swab rinse. Thus, the analyzer developed in this study has the potential to rapidly detect SARS-CoV-2 and other respiratory pathogens on site in a “raw-sample-in and answer-out” manner.